98.2k views
3 votes
3w = -27 (equation) ​

User Alaa Gamal
by
5.3k points

2 Answers

1 vote

Answer:

w = -9

Explanation:

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

3*w-(-27)=0

Step by step solution :

Step 1: Pulling out like terms

Pull out like factors :

3w + 27 = 3 • (w + 9)

Equation at the end of step 1:

Step 2:

Equations which are never true:

Solve : 3 = 0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation:

Solve : w+9 = 0

Subtract 9 from both sides of the equation :

w = -9

One solution was found :

w = -9

User Enamrik
by
5.5k points
2 votes
W=-9

Explanation: 3w=-27

Divide 3 from -27

-27 divided by 3 = -9
User ESR
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.